Ferulic Acid Ameliorates Lipopolysaccharide-Induced Barrier Dysfunction via MicroRNA-200c-3p-Mediated Activation of PI3K/AKT Pathway in Caco-2 Cells - He, Shasha; Guo, Yuhong; Zhao, Jingxia; Xu, Xiaolong; Wang, Ning; Liu, Qingquan (Frontiers in Pharmacology, 2020)
Intestinal barrier dysfunction is an important clinical problem in various acute and chronic pathological conditions. Ferulic acid (FA) can attenuate the intestinal epithelial barrier dysfunction, however, the underlying mechanism remains unclear. The present study aimed to uncover the protective effect of FA on intestinal epithelial barrier dysfunction in a Caco-2 cell model of lipopolysaccharide (LPS) stimulation and the underlying mechanism. Caco-2 cells were pretreated with FA and then exposed to LPS stimulation. The barrier function of Caco-2 cells was evaluated by measuring trans-epithelial resistance (TER) and 4-kDa fluorescein isothiocyanate (FITC)-dextran (FD4) flux, and analyzing the tight junction protein expression and structure. The results showed that decreased TER and increased FITC-FD4 flux were observed in Caco-2 cells stimulated with LPS, but these effects were attenuated by FA pretreatment. FA pretreatment inhibited LPS-induced decrease in occludin and ZO-1 mRNA and protein expression. LPS stimulation decreased miR-200c-3p expression, whereas this decrease was inhibited by FA pretreatment. Furthermore, overexpression of miR-200c-3p strengthened the protective effects of FA on LPS-induced Caco-2 cell barrier dysfunction by decreasing epithelial permeability, increasing occludin and ZO-1 protein expression, and maintaining of ZO-1 protein distribution, while suppression of miR-200c-3p reversed the protective effects of FA. LPS treatment increased the expression of PTEN protein and decreased expression of phosphorylated PI3K and AKT proteins. However, pretreatment of FA inhibited expression of PTEN protein and promoted activation of PI3K/AKT signaling pathway in the LPS-treated Caco-2 cells, and this regulatory effect of FA on the PTEN/PI3K/AKT signaling pathway was strengthened or weakened by miR-200c-3p overexpression or suppression, respectively. Our findings suggested that in Caco-2 cells, FA promotes activation of PI3K/AKT pathway by miR-200c-3p-mediated suppression of the negative mediator PTEN, which, in turn, maintains TJ function and thus ameliorates LPS-induced intestinal epithelial barrier dysfunction.